Chronic sleep restriction differentially affects implicit biases toward food among men and women: preliminary evidence. (2nd November 2017) - Alkozei, Anna; Killgore, William D. S.; Smith, Ryan; Dailey, Natalie S.; Bajaj, Sahil; Raikes, Adam C.; Haack, Monika
Summary: Chronic sleep restriction and obesity are two major public health concerns. This study investigated how chronic sleep restriction changes implicit attitudes towards low‐ and high‐calorie foods. In a randomized, counterbalanced cross‐over design, 17 participants (eight females, nine males) underwent two laboratory testing sessions where they were either sleep‐restricted for 3 weeks (i.e. underwent three weekly cycles of 5 nights of 4 h of sleep followed by 2 nights of 8 h of sleep opportunity) or received 3 weeks of control sleep (i.e. 8 h of sleep opportunity per night for 3 weeks). There was evidence for a significant sleep condition x sex interaction ( F (1, 20)  = 4.60, P  = 0.04). After chronic sleep restriction, men showed a trend towards a significant decrease in their implicit attitudes favouring low‐calorie foods ( P  = 0.08), whereas women did not show a significant change ( P  = 0.16). Men may be at increased risk of weight gain when sleep‐deprived due to a reduced bias towards low‐calorie foods.